The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7556/jaoa.2017.029
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sunburn Risk Among Florida Residents

Abstract: Sunburn prevention programs that osteopathic physicians can readily implement in clinical practice are urgently needed, particularly for young adult patients. This study identified 7 predictors of sunburn in Florida residents. With additional research findings, promoting attitude change toward sun protection may be a viable strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The findings among sun-sensitive individuals are a unique aspect of this article. Previous publications have focused on non-Hispanic white individuals because of the high rates of skin cancer within that demographic group. However, a focus on sun sensitivity is more informative given the increasing racial and ethnic diversity within the US population.…”
Section: Discussionmentioning
confidence: 99%
“…The findings among sun-sensitive individuals are a unique aspect of this article. Previous publications have focused on non-Hispanic white individuals because of the high rates of skin cancer within that demographic group. However, a focus on sun sensitivity is more informative given the increasing racial and ethnic diversity within the US population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in adult populations have reported a frequent lifetime history of at least one sunburn ( Holman et al, 2018 ; Arutyunyan et al, 2017 ; Pinault & Fioletov, 2017 ), with beachgoers as the highest risk group ( Toro-Huamanchumo et al, 2019 ; Troya-Martín et al, 2018 ). Sun sensitivity, a younger age, having a high perceived vulnerability to skin cancer, and having had a full-body skin examination by a physician have been reported as factors associated with sunburns among US adults ( Holman et al, 2018 ; Arutyunyan et al, 2017 ). Similarly, a younger age, male sex, secondary or university education, skin phototypes I–III, midday sun exposure, and lousy sun protection habits have been reported as predictors of sunburns among Spanish beachgoers ( Troya-Martín et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both UVA (320‐400 nm) and UVB (280‐320 nm) contribute to this response known as sunburn, although UVB (280‐320 nm) is more potent in this regard . Sunburn response varies widely among individuals depending on skin type (ie people with lighter skin tone have a greater sunburn risk) and within the same person depending on factors such as age and diet …”
Section: Introductionmentioning
confidence: 99%
“…Both UVA (320-400 nm) and UVB (280-320 nm) contribute to this response known as sunburn, although UVB (280-320 nm) is more potent in this regard. 4 Sunburn response varies widely among individuals depending on skin type (ie people with lighter skin tone have a greater sunburn risk) and within the same person depending on factors such as age 5 and diet. 6,7 In experimental models, sunburn sensitivity is measured using the minimal erythema dose (MED), defined as the smallest UV dose producing perceptible skin redness within distinct borders in a given period of time after exposure.…”
Section: Introductionmentioning
confidence: 99%